The Variability of Thymol and Carvacrol Contents Reveals the Level of Antibacterial Activity of the Essential Oils from Different Accessions of Oliveria decumbens - Tahereh Khoshbakht; Akbar Karami; Aminallah Tahmasebi; Filippo Maggi (MDPI AG, 2020)
Oliveria decumbens (Apiaceae) is an aromatic herb traditionally employed in the Persian medicine for the treatment of infectious and gastrointestinal disorders. In the present study, we analyzed the chemical composition of essential oils obtained from different Iranian populations and evaluated their efficacy on a panel of human pathogens (Staphylococcus aureus and Escherichia coli), probiotic (Bacillus subtilis), and phytopathogens (Clavibacter michiganensis, Curtobacterium flaccumfaciens, Xanthomonas citri, and Agrobacterium tumefaciens). The gas chromatographic-mass spectrometry analysis put in evidence four main volatile constituents such as thymol (20.3-36.4%), carvacrol (18.8-33.1%), γ-terpinene (10.6-25.9%), and p-cymene (9.5-17.3%), though with significant variability from an essential oil to another. Notably, the oils from the populations sited in Nourabad Mamasani and Dehdasht showed the highest amount of the phenolic monoterpenes thymol (36.4 and 35.2%, respectively) and carvacrol (33.1 and 30.6%, respectively). The antibacterial activity of O. decumbens essential oils was assessed by the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods, showing high activity for the samples from Nourabad Mamasani and Dehdasht populations exhibiting high level of the above phenolics. The obtained MIC and MBC values (mg/ml) were in the ranges 0.0625-2 mg/ml and 1-16 mg/ml, respectively. Noteworthy, in some cases, the antibacterial activity of O. decumbens essential oils was higher than that of chloramphenicol used as positive control. The average MBCs displayed by the O. decumbens samples showed that C. flaccumfaciens had the highest sensitivity to the essential oils. Based on these results, our work shed light on selected O. decumbens populations deserving proper breeding and cultivation strategies in order to warrantee production of bioactive essential oils to be used at pharmaceutical and agricultural level to combat several pathogens.